Form of Presentation of Jaranan Buto Wargo Budoyo in Labuhan Sumbawa Village, Labuhan Badas District, Sumbawa Regency - Damanik, Desy Wulan Pita Sari; Indah Ayu Saputri (PT Inovasi Pratama Internasional, 2023)
Jaranan Arts Buto is an art originating from Banyuwangi and growing outside Banyuwangi and even outside Java. One of them is Jaranan Art Buto wargo Budoyo is a dance work that developed in the Sumbawa region, to be precise in the Five Residents Hamlet, Labuhan Sumbawa Village, Labuhan Badas District, Sumbawa Regency, West Nusa Tenggara. Properties used in the jaranan dance buto is a horse with the character buto . Where buto is a giant known as evil in Javanese mythology whose shape is like the shape of a horse but has a giant character. The use of horses in Jaranan art Buto wargo Budoyo has a philosophy of fighting spirit. Collecting data using interviews, observation and documentation. This study aims to determine the form of serving jaranan buto wargo budoyo such as movement, accompaniment, makeup and clothing, and things that support this art. This study analyzes the form of presentation of jaranan buto wargo budoyo in Labuhan Sumbawa using descriptive method is a qualitative research. The study used ethnographic methods from James P. Spradley's book. Ethnography consists of research techniques, ethnographic theories, and various kinds of describing culture. The approach used in this paper is choreography. The reference book that refers to the approach used is Y Sumandiyo Hadi's book with the title of content technique form . This research was able to find out the development and form of serving Jaranan Buto wargo Budoyo in the midst of the Labuhan Sumbawa community, Sumbawa district. Then so that it can be analyzed in written form by the next generation from generation to generation so that this art is still running today.